ROMANIA’S YOUNGEST TOWNS – HOW URBAN ARE THEY? - Nóra-Csilla VERESS (Studia Universitatis Babeş-Bolyai: Geographia, 2016)
Romania’s Youngest Towns – How Urban Are They? After the collapse of the socialist regime, the urban system of Romania has changed significantly in a very short period of time: in a few years 60 rural settlements gained the town status, mostly without matching the quantitative and qualitative conditions set by the law. This paper examines those 17 indicators necessary to become a town, and compares the values of 2004 (the year, when a “mass declaration” was conducted which resulted in 38 new towns) with the values of 2014 (the latest available statistical data) in order to see the extent and direction in which the new towns developed (or not) in ten years after becoming urban. The paper discusses also the question of whether urbanization and development can be made via political decisions or not.